PELAKSANAAN AKTIVITAS EKSTRAKURIKULER PASUKAN PENGIBAR BENDERA (PASKIBRA) DALAM PEMBENTUKKAN KARAKTER DISIPLIN SISWA SEKOLAH MENENGAH DI SMPN 2 BOJONGPICUNG - Endang Sawitri; Widya Virtha; Neng Nani; Nandang Rusmana; Dinny Mardiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the implementation of Flag-Raising Troop (Paskibra) extracurricular activities and to analyze their contribution to shaping students’ disciplinary character at SMPN 2 Bojongpicung. The study is grounded in the importance of discipline as a key pillar of student success within the context of the Merdeka Curriculum, which emphasizes the Profile of Pancasila Students and a positive school culture. A qualitative approach with a case study design was employed. The research subjects consisted of the principal, vice principal, Paskibra coach, and Paskibra members from grades VII, VIII, and IX. Data were collected through in-depth interviews, participant and non-participant observations of training sessions and flag ceremony implementation, as well as documentation studies of the school operational curriculum, extracurricular programs, school rules, and student discipline records. Data were analyzed using Miles and Huberman’s model, including data collection, reduction, display, and conclusion drawing, supported by source, technique, and time triangulation to ensure data validity. The findings show that Paskibra at SMPN 2 Bojongpicung is systematically designed, integrated with the school’s vision and mission, and emphasizes the habituation of time discipline, neatness, compliance with rules, and role modeling by the coach. Regular training, flag-raising duties, and positive routines positively impact students’ punctuality, rule compliance, sense of responsibility, independence, and self-confidence. Thus, Paskibra serves as a strategic vehicle for developing students’ disciplinary character at the secondary school level that is important to maintain and further strengthen.